Benzamil sensitive ion channels contribute to volume regulation in canine chondrocytes. (12th March 2013) - Lewis, R; Feetham, CH; Gentles, L; Penny, J; Tregilgas, L; Tohami, W; Mobasheri, A; Barrett‐Jolley, R
Abstract : Background and Purpose: Chondrocytes exist within cartilage and serve to maintain the extracellular matrix. It has been postulated that osteoarthritic (OA) chondrocytes lose the ability to regulate their volume, affecting extracellular matrix production. In previous studies, we identified expression of epithelial sodium channels (ENaC) in human chondrocytes, but their function remained unknown. Although ENaC typically has Na + transport roles, it is also involved in the cell volume regulation of rat hepatocytes. ENaC is a member of the degenerin (Deg) family, and ENaC/Deg‐like channels have a low conductance and high sensitivity to benzamil. In this study, we investigated whether canine chondrocytes express functional ENaC/Deg‐like ion channels and, if so, what their function may be. Experimental Approach: Canine chondrocytes were harvested from dogs killed for unassociated welfare reasons. We used immunohistochemistry and patch‐clamp electrophysiology to investigate ENaC expression and video microscopy to analyse the effects of pharmacological inhibition of ENaC/Deg on cell volume regulation. Key Results: Immunofluorescence showed that canine chondrocytes expressed ENaC protein. Single‐channel recordings demonstrated expression of a benzamil‐sensitive Na + conductance (9 pS), and whole‐cell experiments show this to be approximately 1.5 nS per cell with high selectivity for Na + . Benzamil hyperpolarized chondrocytes by approximately 8 mV with a pD2 8.4. Chondrocyte regulatory volume decrease (RVI) was inhibited by benzamil ( pD2 7.5) but persisted when extracellular Na + ions were replaced by Li + . Conclusion and Implications: Our data suggest that benzamil inhibits RVI by reducing the influx of Na + ions through ENaC/Deg‐like ion channels and present ENaC/Deg as a possible target for pharmacological modulation of chondrocyte volume.